Application of genetic algorithm methods to optimize flowshop sequencing problem - Mohd Fadil, Md Sairi (2008)
Application of genetic algorithm method to optimize flow shop sequencing problem as the title of this project is the study about the method used in order to optimize flow shop sequencing problem. Genetic algorithm method was one of the methods that were widely used in solving optimization problem. Genetic algorithm method is methods that follow the natural concept. Flow shop sequencing problem or also known as assembly line problem that normally faced by production company. This project will define the application of genetic algorithm method in solving flow shop sequencing problem in details and evaluate the strength and weakness of genetic algorithm method in order to optimize the optimization problem. This project will focusing on the method used to solve an optimization problem, the limitation of the method used and the results of solving flow shop sequencing problem using genetic algorithm method. At the end of this project, we can see the performance of genetic algorithm method in solving flow shop sequencing problem and types of flow shop sequencing problems that can be solve through genetic algorithm method. Limitation of genetic algorithm method also can be shown at the end of this project.